Influence of thickeners (microfibrillated cellulose, starch, xanthan gum) on rheological, tribological and sensory properties of low-fat mayonnaises. (March 2023) - Blok, Annelies E.; Bolhuis, Dieuwerke P.; Arnaudov, Luben N.; Velikov, Krassimir P.; Stieger, Markus
Abstract: Microfibrillated cellulose (MFC) is obtained by high-shear treatment of cellulose. MFC is suitable for use as clean-label, low-calorie thickener in semi-solid foods such as mayonnaises due to its high water holding capacity. The aim of this study was to determine the effect of type and concentration of thickener on rheological, tribological and sensory properties of low-fat mayonnaises. Low-fat mayonnaises were prepared with four types of thickeners (MFC, chemically modified starch, native waxy corn starch, xanthan gum) at three concentrations. Higher biopolymer concentrations resulted in increased shear viscosities, G′ and G″, yield stress and enhanced lubrication ( i.e. lower friction coefficients). Mayonnaises with modified starch and xanthan gum generally had higher shear viscosity and yield stress compared to mayonnaises with comparable concentrations of MFC and waxy corn starch. MFC-thickened mayonnaises had highest G', G" and boundary friction coefficients. Sensory properties of mayonnaises were determined using the Rate-All-That-Apply (RATA) method ( n  = 80). Addition of xanthan gum induced high sliminess and pulpiness, and low melting, creaminess and smoothness. Sensory properties of mayonnaises with MFC were generally similar to those with modified and waxy corn starch, despite differences in appearance (increased yellowness and slightly lower glossiness). Multiple Factor Analysis revealed that more shear-thinning mayonnaises were perceived as slimy. Boundary friction was negatively correlated with stickiness, while friction at the start of the hydrodynamic regime was positively correlated with melting sensations. We conclude that microfibrillated cellulose can be used as a thickener in low-fat mayonnaise as an alternative to commercially used chemically modified starch without considerably affecting its sensory texture properties. Graphical abstract: Image 1 Highlights: Low-fat mayonnaises were thickened with microfibrillated cellulose (MFC), xanthan gum, chemically modified or native waxy corn starch. Effect of thickener type and concentration on rheological, tribological and sensory properties was studied. MFC-thickened mayonnaises had highest G′, G″ and boundary friction. Sensory texture of mayonnaises with MFC was similar to those thickened with starch. Mayonnaises with xanthan gum were slimier and pulpier; but less smooth, creamy and melting.